Phytopathology in Plants 2016
DOI: 10.1201/b13127-6
|View full text |Cite
|
Sign up to set email alerts
|

- Enhanced Disease Susceptibility 1 and Salicylic Acid Act Redundantly to Regulate Resistance Gene-Mediated Signaling

Abstract: For successful colonization and further reproduction in host plants, pathogens need to overcome the innate defenses of the plant. We demonstrate that a novel pathogenicity gene, DES1, in Magnaporthe oryzae regulates counter-defenses against host basal resistance. The DES1 gene was identified by screening for pathogenicity-defective mutants in a T-DNA insertional mutant library. Bioinformatic analysis revealed that this gene encodes a serine-rich protein that has unknown biochemical properties, and its homologs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 55 publications
(71 reference statements)
0
54
0
Order By: Relevance
“…However, unlike in des1Δ and sir2Δ, treatment with the exogenous antioxidants GSH or DPI does not suppress abmΔ-induced accumulation of inclusions in rice plants. Furthermore, though the des1Δ mutant is hypersensitive to exogenous oxidative stress 33 , the abmΔ did not show any sensitivity toward hydrogen peroxide during mycelial growth. In contrast, loss of the M. oryzae glutathione peroxidase Hyr1, whose function is to break down ROS in planta 36 , does not induce deposition of granules or inclusions during host invasion.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, unlike in des1Δ and sir2Δ, treatment with the exogenous antioxidants GSH or DPI does not suppress abmΔ-induced accumulation of inclusions in rice plants. Furthermore, though the des1Δ mutant is hypersensitive to exogenous oxidative stress 33 , the abmΔ did not show any sensitivity toward hydrogen peroxide during mycelial growth. In contrast, loss of the M. oryzae glutathione peroxidase Hyr1, whose function is to break down ROS in planta 36 , does not induce deposition of granules or inclusions during host invasion.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, fungal Abm activity most likely prevents the basal host defense response by keeping phytoalexin levels in check during establishment of the blast fungus. A number of M. oryzae mutants that are impaired in suppressing the basal defense response in rice [33][34][35] , such as des1Δ, sir2Δ and snx41Δ, show increased accumulation of granular deposits, which resemble the inclusions triggered by abmΔ in the invaded rice cells. However, unlike in des1Δ and sir2Δ, treatment with the exogenous antioxidants GSH or DPI does not suppress abmΔ-induced accumulation of inclusions in rice plants.…”
Section: Discussionmentioning
confidence: 98%
“…With respect to the toxicity of ROS molecules and their importance in plant defense responses, plant pathogens have to develop strategies to scavenge ROS for survival in harsh environments and successfully invade host cells [47]. In fungal plant pathogens, several genes have proven to be responsible for ROS detoxification at the infection site, and the defects of these corresponding genes have shown attenuated virulence on host plants [25,27]. In this study, we found that the PsGcn5-silenced mutant had no apparent defects in hyphae growth and cyst germination, but had limited infectious hyphae growth and reduced virulence in the susceptible soybean cv.…”
Section: Discussionmentioning
confidence: 99%
“…During the interactions between plants and pathogens, scavenging of host-derived ROS at the site of infection is a key mechanism for pathogens to overcome plant defenses and colonise the host [25,27]. We hypothesized that the blocked hyphal growth in the infected cell and reduced virulence of the PsGcn5-silenced mutant were due to a defect in the scavenging of ROS.…”
Section: Psgcn5 Is Required For Suppressing the Production Of Ros In mentioning
confidence: 99%
See 1 more Smart Citation